Pribumisasi Makna Al-Qur’an dalam Tafsir Vernakular: Analisis Hermeneutika Gadamer atas al-Ibrīz dan Raudatul ‘Irfān pada Horizon Jawa–Sunda - Asyfia, Wildan Rifqi (Tashwirul Afkar, 2026)
This study aims to identify, describe, and compare strategies of indigenizing interpretation (pribumisasi) in two vernacular Qur’anic commentaries (tafsir) from the Indonesian archipelago, namely al-Ibrīz li Ma‘rifati Tafsir al-Qur’an al-‘Azīz (Javanese horizon) and Raudatul ‘Irfān fi Ma‘rifat al-Qur’an (Sundanese horizon), with particular attention to how locality operates as a mechanism of understanding that mediates between the horizon of the text and the horizon of the reader. The research employs a qualitative-interpretive design grounded in textual analysis and hermeneutics, using documentation study and close reading of four units of analysis (J1: Q. an-Nūr [24]:27; J2: Q. al-Qaṣaṣ [28]:70; S1: Q. al-Baqarah [2]:217; S2: Q. al-‘Ankabūt [29]:41). Findings are analyzed through categorization across three comparable dimensions and operationalized through Hans-Georg Gadamer’s hermeneutical framework (the text–reader horizon relation, pre-understanding, tradition/authority, effective history, and the fusion of horizons). The results show that al-Ibrīz grounds meaning through the social-ethical diction kulo nuwun and the relational–hierarchical metaphor sowan, employing a dialogical-procedural pedagogical style, whereas Raudatul ‘Irfān foregrounds local calendrical diction (Hapit–Rayagung) and local fauna metaphors (lancah/ramat lancah), reinforced by descriptive elaborations of nature in an explanatory mode. In terms of implications, these findings underscore the need for follow-up actions in the domains of tafsir curricula (integrating Tafsir Nusantara as a hermeneutical case-study module), editorial standards (mandatory glossaries and paratexts for cultural terms), da‘wah/educational strategies (controlled use of local equivalents accompanied by explicit textual-meaning boundaries), and the digitalization of annotated editions to broaden cross-community access. The originality of this study lies in its comparison of two cultural horizons (Javanese–Sundanese) within a single analytical design using an equivalent-dimensional matrix, its deployment of Gadamer as an “analytical engine” to trace meaning-formation processes systematically through specific textual units, and its reading of indigenization as a communicative-interpretive strategy balanced by a critical reflection on the risks of dysfunction.